A Study Of The Effect Of Particle Fractal Geometry On Flotation Performance - M. Burstein; S. T. Hall; A. A. Kornyshev (Society for Mining, Metallurgy & Exploration, 1995)
The surface "roughness" of mineral particles has long been known to influence the fundamental process of particle-bubble attachment and other subprocesses in froth flotation. The physical nature of the surface of fine mineral particles can be analysed by determining their fractal geometry. A number of techniques are available to measure the fractal properties of mineral particles, these include gas adsorption, mercury porosimetry, neutron or X- ray scattering and image analysis. From the resultant Richardson plots or their Fourier-space analogs, the fractal dimension of flotation feed and product samples can be determined. Textural characteristics of particles have an influence on the stability of 3-phase flotation froths and the selectivity of recovery in the froth. Decrease of the equilibrium froth height for particles of higher fractal dimensions was experimentally established. The induction time of quartz particles of different fractal geometry has also been studied.